Study of knowledge, attitudes and practices of complementary feeding among caregivers of children from 6 to 23 months of age from a rural community of Ecuador: A cross-sectional study. - Rocío Lara; Katherine García; Luz Valencia; Alfonso Silva (Revista Española de Nutrición Humana y Dietética)
Introduction. Nutritional deficiency due to an unbalanced diet is one of the most important factors contributing to stunting or the development of comorbidities in infants. Poverty, lack of knowledge about complementary feeding (CF) schedules, or lack of information accessibility are among the major causes that affect nutritional status. Our objective was to investigate the association of caregivers' knowledges, attitudes, and CF practices with the nutritional status of children aged 6 to 23 months attending the Camilo Ponce Enriquez Health Center from October to December 2022.